2010
DOI: 10.1104/pp.110.168716
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-1-Phosphate Transport into Protoplasts and Chloroplasts from Leaves of Arabidopsis

Abstract: Almost all glucosyl transfer reactions rely on glucose-1-phosphate (Glc-1-P) that either immediately acts as glucosyl donor or as substrate for the synthesis of the more widely used Glc dinucleotides, ADPglucose or UDPglucose. In this communication, we have analyzed two Glc-1-P-related processes: the carbon flux from externally supplied Glc-1-P to starch by either mesophyll protoplasts or intact chloroplasts from Arabidopsis (Arabidopsis thaliana). When intact protoplasts or chloroplasts are incubated with [U-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 44 publications
1
77
0
Order By: Relevance
“…First, bioinformatic analysis of Arabidopsis metabolite profiles revealed patterns suggestive of microcompartmentation of metabolism within organelles (Krueger et al, 2011), as previously postulated for a pool of UDPG that is involved in cellulose synthesis (Amor et al, 1995). Secondly, recent studies in Arabidopsis and potato implicate the presence of as yet unidentified G1P transporters at the plastid and plasma membranes (Fettke et al, 2011). Further analyses will be required to fully understand the exact mechanisms by which the active and inactive pools of these metabolites are separated.…”
Section: Discussionmentioning
confidence: 99%
“…First, bioinformatic analysis of Arabidopsis metabolite profiles revealed patterns suggestive of microcompartmentation of metabolism within organelles (Krueger et al, 2011), as previously postulated for a pool of UDPG that is involved in cellulose synthesis (Amor et al, 1995). Secondly, recent studies in Arabidopsis and potato implicate the presence of as yet unidentified G1P transporters at the plastid and plasma membranes (Fettke et al, 2011). Further analyses will be required to fully understand the exact mechanisms by which the active and inactive pools of these metabolites are separated.…”
Section: Discussionmentioning
confidence: 99%
“…1). Both zones are undetectable in PHS2-deficient Arabidopsis mutants but present in the mutants lacking PHS1 (Lu et al, 2006;Fettke et al, 2011a). It is, however, not clear what actually causes the partitioning between the immobile and the more mobile state.…”
mentioning
confidence: 91%
“…The phosphoglucose isomerase (PGI) converts Fru-6-P to Glc-6-P; then, Glc-6-P is converted to Glc-1-P by phosphoglucomutase (PGM); Glc-1-P is then metabolized to ADP-Glc by ADP-Glc pyrophosphorylase (AGPase). However, there is ongoing discussion over the origin of the residual starch (3%-15%) in some null mutants of the plastidic PGI-PGM-AGPase pathway (Niewiadomski et al, 2005;Streb et al, 2009;Kunz et al, 2010;Bahaji et al, 2015), the significance of the observed uptake of exogenously applied Glc-1-P to isolated chloroplasts and its conversion to starch (Fettke et al, 2011), the disputed possibility of an alternative cytosolic route of ADP-Glc synthesis by Suc synthase (SUS) and its potential translocation to the chloroplast (Muñoz et al, 2005;Barratt et al, 2009;Baroja-Fernández et al, 2012;Smith et al, 2012), and the recently suggested PGI1-independent starch synthesis (Bahaji et al, 2015). Starch synthesis in nonphotosynthetic plastids relies on the translocation of carbon from the cytosol, mainly in the form of hexose phosphate (Flügge, 1999).…”
mentioning
confidence: 99%